A novel LRR-only protein mediates bacterial proliferation in hemolymph through regulating expression of antimicrobial peptides in mollusk Chlamys farreri. (March 2019) - Wang, Mengqiang; Wang, Baojie; Liu, Mei; Jiang, Keyong; Wang, Lei
Abstract: Leucine-rich repeat (LRR)-only proteins are involved in innate immune responses through mediating protein-ligand or protein-protein interactions, yet the exact roles of most LRR-only proteins in invertebrates are not well documented. In the present study, a novel LRR-only protein (designated Cf LRRop-7) was identified in Zhikong scallop Chlamys farreri . The full-length cDNA sequence of Cf LRRop-7 was 1463 bp and contained an open reading frame of 1086 bp, which encoded a protein of 361 amino acids. Five LRR motifs with a conserved signature sequence LxxLxLxxNxL were identified in the predicted protein sequence. The expression of Cf LRRop-7 was particularly high in hemocytes. The expression of Cf LRRop-7 was relatively high in oocytes and embryos during the ontogenesis of scallops. Cf LRRop-7 expression changed in hemocytes in response to stimulation with different microbes, including Vibrio splendidus, Staphylococcus aureus and Pichia pastoris . Cf LRRop-7 recognized five kinds of ligands/agonists. Cf LRRop-7 recombinant protein inhibited bacterial proliferation in hemolymph and induced lysozyme activity in serum. After knocking down Cf LRRop-7, the mRNA expression of selected antimicrobial peptides was reduced. All these results indicated that Cf LRRop-7 might be a potential pattern recognition receptor that recognizes various pathogen associated molecular patterns, and regulates antibacterial immunity in scallops. Highlights: A novel LRR-only protein ( Cf LRRop-7) was identified in scallop Chlamys farreri . Cf LRRop-7 exhibited recognition capacity to various PAMPs. Cf LRRop-7 inhibits the bacterial proliferation by regulating expression of antimicrobial peptides.